Experimental research and HHT analysis on the flow characteristics of pneumatic conveying under high pressure. (5th September 2016) - Lu, Peng; Li, Wei; Zheng, Xingwen; Chen, Xiaoping; Zhao, Changsui
Highlights: Mechanism affecting the flow characteristics of pneumatic conveying was revealed. Hilbert-Huang transform and experiments were conducted on the influence factors. Energy distribution of pressure signal reflects the flow regime & characteristics. Some of the results have also been verified by numerical simulation. Abstract: Pneumatic conveying under high pressure plays an important role in coal gasification. Reveal of the underlying mechanism affecting the conveying characteristics, especially the flow regime, is of great significance. Due to strong adhesion to the pipe wall of coal powder with particle size smaller than 120 μm, direct optical observation is very difficult. By combining HHT analysis and experiments, investigation on the flow regime of pulverized coal with 300 μm was proved feasible. Then this method was applied to pulverized coal with smaller size, focusing on the influences of superficial gas velocity, particle size, and conveying pressure, respectively. The results indicate that as superficial gas velocity reduces, the coal particles gradually deposit onto the bottom of the pipeline, with lower moving speed and lower-frequency collisions. Coal powder with smaller particle size is relatively easy to be carried by conveying gas flow to form suspended flow, whereas pulverized coal with larger size tends to fall down onto the bottom and form a settled layer. In addition, pneumatic conveying under higher pressure will lead to lower superficial gas velocity and higher solid-gas ratio, which consequently causes the particles to slow down and drop onto the bottom, with the collisions less intense and frequent.